Promoter of conservation tillage and erosion control: Life and work of Dr. Benjamín Figueroa Sandoval - Espinosa-Victoria, David; Figueroa-Rodríguez, Oscar Luis (REVISTA TERRA LATINOAMERICANA, 2020)
The Mexican Soil Science Society, C.A. (MSSS), gives a deep of post-mortem recognition to Dr. Benjamín Figueroa Sandoval, one of its most distinguished and active members. Dr. Figueroa Sandoval was born on April 30, 1949 in Guadalajara, Jalisco, México, and died on February 21, 2020 in Salinas de Hidalgo, San Luis Potosí, México. His scientific work included the areas of research: sustainable agriculture, conservation tillage and soil physics. In addition to being an excellent soil scientist, he had among his hobbies the sport, being a football fan and basketball player, as well as reading and music. Dr. Figueroa Sandoval served as General Director of the Colegio de Postgraduados for two consecutive periods, from 1999 to 2003 and from 2004 to 2007. Much of his scientific legacy is embodied in the records of MSSS, CA.